Sustainable microalgal biomass valorization to bioenergy: Key challenges and future perspectives. (June 2022) - Tawfik, Ahmed; Ismail, Sherif; Elsayed, Mahdy; Qyyum, Muhammad Abdul; Rehan, Mohammad
Abstract: The global trend is shifting toward circular economy systems. It is a sustainable environmental approach that sustains economic growth from the use of resources while minimizing environmental impacts. The multiple industrial use of microalgal biomass has received great attention due to its high content of essential nutrients and elements. Nevertheless, low biomass productivity, unbalanced carbon to nitrogen (C/N) ratio, resistant cellular constituents, and the high cost of microalgal harvesting represent the major obstacles for valorization of algal biomass. In recent years, microalgae biomass has been a candidate as a potential feedstock for different bioenergy generation processes with simultaneous treating wastewater and CO2 capture. An overview of the appealing features and needed advancements is urgently essential for microalgae-derived bioenergy generation. The present review provides a timely outlook and evaluation of biomethane production from microalgal biomass and related challenges. Moreover, the biogas recovery potential from microalgal biomass through different pretreatments and synergistic anaerobic co-digestion (AcoD) with other biowastes are evaluated. In addition, the removal of micropollutants and heavy metals by microalgal cells via adsorption and bioaccumulation in their biomass is discussed. Herein, a comprehensive review is presented about a successive high-throughput for anaerobic digestion (AD) of the microalgal biomass in order to achieve for sustainable energy source. Lastly, the valorization of the digestate from AD of microalgae for agricultural reuse is highlighted. Graphical abstract: Image 1 Highlights: Biomethane recovery potential from algal biomass is evaluated. Technical harvesting methods of algal biomass are reviewed. Microalgae is a great low-cost contender for biogas fermentation. Algal biomass to bioenergy offers good environmental remediations. Key challenges and opportunities of sustainable algal biomass valorization to bioenergy.